HOX Genes in Pancreatic Development and Cancer - Gray, Sophie; Pandha, Hardev S; Michael, Agnieszka; Middleton, Gary; Morgan, Richard (JOP. Journal of the Pancreas, 2011)
The HOX genes are a family of homeodomain-containing transcription factors that determine cellular identity during development and which are subsequently re-expressed in many types of cancer. Some recent studies have shown that HOX genes may have key roles both in pancreatic development and in adult diseases of the pancreas, including cancer. In this review we consider recent advances in elucidating the role of HOX genes in these processes, how they may connect early developmental events to subsequent adult disease, and their potential both as diagnostic markers and therapeutic targets. Image: The arrangement of HOX genes in the mammalian genome.